Significant association of SREBP-2 genetic polymorphisms with avascular necrosis in the Korean population - Park Eui; Cho Hyun-Ju; Lee Hye-Jin; Choi Su-Jin; Hong Jung; Baek Jeong-In; Kim Tae-Ho; Kim Un-Kyung; Kim Shin-Yoon (BMC, 2008)
Abstract Background It is known that steroid usage and alcohol abuse are major etiological factors in the development of avascular necrosis (AVN), a bone disease that produces osteonecrosis of the femoral head. The facilitation of fat biosynthesis by steroids and alcohol disrupts the blood supply into the femoral head. SREBP-2 plays a central role in the maintenance of lipid homeostasis through stimulating expression of genes associated with cholesterol biosynthetic pathways. The aim of this study was to examine the association between the polymorphisms of the SREBP-2 gene and AVN susceptibility in the Korean population. Methods Four single nucleotide polymorphisms (SNP) in the SREBP-2 gene, IVS1+8408 T>C (rs2267439), IVS3-342 G>T (rs2269657), IVS11+414 G>A (rs1052717) and IVS12-1667 G>A (rs2267443), were selected from public databases and genotyped in 443 AVN patients and 273 control subjects by using single-based extension (SBE) genotyping. Results The minor allele (C) frequency of rs2267439 showed a significant protective effect on AVN (P = 0.01, OR; 0.75, 95% CI; 0.604-0.935), and the genotype frequencies of this polymorphism were also different from the controls in all alternative analysis models (P range, 0.009-0.03, OR; 0.647-0.744). In contrast, rs1052717 and rs2267443 polymorphisms were significantly associated with AVN risk. Further analysis based on pathological etiology showed that the genotypes of rs2267439, rs1052717 and rs2267443 were also significantly associated with AVN susceptibility in each subgroup. Conclusion This study is the first report to evaluate the association between SREBP-2 gene polymorphisms and the susceptibility of AVN in the Korean population.